PENGARUH PENDIDIKAN KESEHATAN DENGAN BOOKLET TERHADAP PENGETAHUAN IBU HAMIL TENTANG PROTOKOL KESEHATAN - Detty Afrianti; Selvia Yuliani Gusrizal (Universitas Fort de Kock Bukittinggi, 2022)
Covid-19 infection in pregnant women has a greater impact than the group of women who are not pregnant. The purpose of this study was to determine the effect of health education booklets on knowledge of pregnant women about health protocols during a pandemic. The design of this research was quasi-experimental with Post-Test Only Non Equivalent Control Group Design approach. The population in the study were 235 pregnant women. Sampling using purposive sampling technique with a sample size of 32 people who were divided into 2 groups. Data collection using a knowledge questionnaire. Data analysis included univariate analysis and bivariate analysis using independent ttest. The results showed that the average post-test knowledge in the control group was 14.37 and the post-test knowledge average in the experimental group was 19.00. There was a difference in the average knowledge of pregnant women between the control group and the experimental group with an average difference of 4.625 and p value = 0.000. It can be concluded that health education using booklets has a significant effect on knowledge of pregnant women about health protocols. Keywords : Health Education, Booklet, Knowledge, Pregnant Women, Health Protocol